2015
DOI: 10.1111/iwj.12416
|View full text |Cite
|
Sign up to set email alerts
|

A review of the surgical management of heel pressure ulcers in the 21st century

Abstract: Heel ulceration, most frequently the result of prolonged pressure because of patient immobility, can range from the trivial to the life threatening. Whilst the vast majority of heel pressure ulcers (PUs) are superficial and involve the skin (stages I and II) or underlying fat (stage III), between 10% and 20% will involve deeper tissues, either muscle, tendon or bone (stage IV). These stage IV heel PUs represent a major health and economic burden and can be difficult to treat. The worst outcomes are seen in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 84 publications
1
24
0
2
Order By: Relevance
“…• a standard of care should be carried out for all diabetic heel ulcer patients; this includes assessment of peripheral vasculature, screening for infection and offloading of the heel • the application of acellular dermal matrices should be considered in patients where flap reconstruction may not be suitable • patients with normal ankle-brachial pressure indices are less likely to demonstrate postoperative complications, for example, wound dehiscence • recent comparative studies have shown no significant differences in the success of free or pedicled flaps between the diabetic and non-diabetic population; all patients had 'adequate vascular supply' prior to flap surgery • partial to complete calcanectomies with concurrent external foot fixation and hindfoot offloading may result in limb salvage this, the close proximity of skin to bone in the heel presents a considerable risk of osteomyelitis when a communicating ulcer lays in situ (5). While the abovementioned factors may be at play against the adequate healing of an ulcer, PVD in particular has been shown to be an important predictive factor for limb loss (14,15).…”
Section: Key Messagesmentioning
confidence: 99%
See 3 more Smart Citations
“…• a standard of care should be carried out for all diabetic heel ulcer patients; this includes assessment of peripheral vasculature, screening for infection and offloading of the heel • the application of acellular dermal matrices should be considered in patients where flap reconstruction may not be suitable • patients with normal ankle-brachial pressure indices are less likely to demonstrate postoperative complications, for example, wound dehiscence • recent comparative studies have shown no significant differences in the success of free or pedicled flaps between the diabetic and non-diabetic population; all patients had 'adequate vascular supply' prior to flap surgery • partial to complete calcanectomies with concurrent external foot fixation and hindfoot offloading may result in limb salvage this, the close proximity of skin to bone in the heel presents a considerable risk of osteomyelitis when a communicating ulcer lays in situ (5). While the abovementioned factors may be at play against the adequate healing of an ulcer, PVD in particular has been shown to be an important predictive factor for limb loss (14,15).…”
Section: Key Messagesmentioning
confidence: 99%
“…Complications commonly seen in diabetic populations include peripheral neuropathy, peripheral vascular disease (PVD), arthropathy, altered biomechanics of the foot and poor wound healing . These risk factors, coupled with intrinsic anatomical vulnerabilities and the pressure‐loading nature of the heel, are accountable for the unique challenges faced in the management of this condition . In addition to this, the close proximity of skin to bone in the heel presents a considerable risk of osteomyelitis when a communicating ulcer lays in situ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in the period 2008 to 2011 around every fifth patient with a major amputation had a secondary diagnosis of dementia (26). In bedridden demented patients with advanced tissue destruction, primary major amputation makes more sense than revascularization (27,28).…”
Section: <00001mentioning
confidence: 99%